Kelas Kesehatan dan Ruang Komunikasi Kesehatan bagi Mahasiswa Indonesia di Korea - Ana Riolina; Ikmal Hafizi; Dendy Murdiyanto; Peni Indrayudha (Abdi Geomedisains, 2025)
The background that underlies this activity is that the cooperation between Indonesia and South Korea in the field of education has opened up opportunities for Indonesian students to continue their studies at several universities in Korea, such as Hankuk University for Foreign Studies and Busan University for Foreign Studies. However, Indonesian students in Korea face challenges in maintaining their health, especially dental and oral health. Language barriers and high treatment costs are the main obstacles in accessing dental health services. Answering existing problems, activities are carried out with methods in the form of community service in the form of health classes and health communication rooms. The targeted goal is to increase the knowledge and awareness of Indonesian students' health in Korea. The course of the activity includes need assessment, preparation of educational materials, implementation of health classes and introduction of teledentistry, as well as evaluation of activities. The results showed that the activity succeeded in increasing students' understanding of the importance of dental and oral care and the use of remote health communication technology. This activity also strengthens the academic network between the University of Muhammadiyah Surakarta and universities in Korea. It is hoped that this activity will become a model of sustainable international service that can be imitated in various other countries.